Implementasi Good Corporate Governance Dalam Mencegah Tindak Pidana Korupsi Pada Badan Usaha Milik Negara - Sutanto, Nadia Nathania; Christie, Amanda; Elviyana, Julia; Simanjuntak, Calvin Paulus; Baharina, Ade Michele Siti Aisyah (PT Matra Cendikia Abadi, 2025)
The implementation of Good Corporate Governance (GCG) in companies plays a crucial role in preventing corruption through principles of transparent, accountable, and responsible governance. This study aims to analyze the effectiveness of GCG implementation as a measure to mitigate corruption and to identify obstacles faced in its application in Indonesia, particularly in State-Owned Enterprises (SOEs). The research method used is normative juridical, with an approach that analyzes regulations related to GCG. The source of data in this research is secondary data, which is obtained through literature studies, including books, journals, official reports, and related regulations such as Law No. 31/1999 on the Eradication of Corruption and regulations on good corporate governance. The results show that although GCG implementation in SOEs has been regulated by various policies, its application is still hindered by weak law enforcement, a lack of transparency culture, and political influence in SOE management. As a result, GCG implementation has not been optimal in preventing corruption. Therefore, strengthening regulations and strict law enforcement are needed, along with organizational cultural changes to integrate GCG principles into company operations.